UJI PENGGUNAAN LIMBAH SAGU SEBAGAI MEDIA TANAM ANGGREK (Dendrobium sp.) - Royana, Ken Qudsy; Prihastanti, Erma (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
Dendrobium orchids are the second largest among the genus of the orchid family (Orchidaceae). Waste derived from sago palm tree waste contained in Plajan. Sago waste are not used optimally so that its existence is very abundant and polluting the surrounding environment, therefore sago waste is used as media for Dendrobium that is expected to reduce enviromental pollution caused by waste and sago can find out what kind of sago waste can provide optimal growth for the growth of orchids. Media used include cocnut husk as a control, fresh sago waste and black sago waste Â with additional media such as charcoal. Pot filled with charcoal third as much as the high pot and then added with coconut conducted in Kajeksan Kudus from 1 August to 7 September 2011 and carried out meassurments of plant height, leaf number, leaf width and length of leaves for one week. The data obtained are presented in tabular form. The study explains that fresh sago waste and black sago waste can have a positive for the growth of orchids and fresh sago waste is a media that can provide optimal growth for orchids. Â  Key Words: Orchid (Dendrobium sp.), coconut fiber, fresh sago waste, black sago waste, charcoal